Prevalence, functional characteristics, and clinical significance of right ventricular involvement in patients with hypertrophic cardiomyopathy - Seo, Jiwon (Sci Rep, 2020)
We sought to investigate the prevalence, functional characteristics, and clinical significance of right ventricular (RV) involvement in patients with hypertrophic cardiomyopathy (HCM). A total of 256 patients with HCM who underwent both cardiac magnetic resonance (CMR) imaging and transthoracic echocardiography within 6 months of each other were retrospectively analysed. RV involvement was defined as an increased RV wall thickness ≥ 7 mm on CMR in the segments of the RV free wall. Primary outcomes were defined as the composite of all-cause death, heart transplantation, and unplanned cardiovascular admission. Thirty-seven (14.4%) patients showed RV involvement. Patients with RV involvement showed a significantly higher left ventricular (LV) maximal wall thickness and left atrial volume index. Multivariate Cox model revealed that RV involvement was independently associated with primary outcomes (HR: 2.30, p = 0.024). In a subgroup analysis of patients with speckle tracking echocardiography (n = 190), those with RV involvement had significantly more impaired RV strain, which was independently associated with primary outcomes. RV involvement in patients with HCM correlated with more advanced LV structure and biventricular dysfunction, suggesting an indicator of severe HCM. RV involvement and impaired RV strain have a prognostic value related to clinical adverse events in patients with HCM.